Quantifying the influence of yellow fluorescent protein photoconversion on acceptor photobleaching-based fluorescence resonance energy transfer measurements - Seitz, Arne; Pepperkok, Rainer (Journal of biomedical optics, 2012)
Fluorescence resonance energy transfer (FRET) efficiency measurements based on acceptor photobleaching of yellow fluorescent protein (YFP) are affected by the fact that bleaching of YFP produces a fluorescent species that is detectable in cyan fluorescent protein (CFP) image channels. The presented quantitative measurement of this conversion makes it possible to correct the obtained FRET signal to increase the accuracy of intensity based CFP/YFP FRET measurements. The described method can additionally be used to compare samples with very different fluorescence levels.